Possibilities of Acmeological Approach in Developing Professional Competence of Future Teachers - Anarbayeva, Muhlisa (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the role and potential of the acmeological approach in developing the professional competence of future teachers. It analyzes the importance of innovative methods, reflection, motivation, and self-development skills in ensuring students’ personal and professional growth. The article presents scientifically grounded conclusions on improving pedagogical education and preparing highly qualified teaching staff.